METACOGNITION LEARNING INFLUENCES THROUGH AN INQUIRY METHOD ON UNDERSTANDING IMPROVEMENT OF SOCIAL SCIENCE EDUCATION CONCEPTS AND CRITICAL THINKING SKILLS OF STUDENTS (A STUDY OF QUASI EXPERIMENT IN CLASS VII AT SMP NEGERI 2 MENES - PANDEGLANG) - Adiarto, Ato (Universitas Pendidikan Indonesia, 2017)
The purpose of this study is to identify the influence of meta-cogenesis learning through an inquiry method in order to increase the understanding of Social Science Education concepts and critical thinking skills of students. This study employed a quantitative approach with quasi experiment method and Pretest Control Group design. The population of this study was the students in class VII at SMPN 2 Menes. With respect to the sample of this study, the class VII B was used as the experimental class by applying metacognition learning through an inquiry method and the Class VII A as the control class that applied a problem-based learning method. The research instrument was a multiple choice form test used to understand the Social Science Education concepts and essay form tests used to measure critical thinking skills, observation sheets and interviews. The data of those aforementioned test results was analyzed quantitatively to measure the means difference between the two sample classes. The results of this study showed (1) there was a difference between the pretest and posttest results on the understanding of Social Science Education concepts and critical thinking skills in the experiment and control classes, (2) there was no significant difference of influences between experiment and control classes in improving the understanding of Social Science Education concepts and critical thinking skills.